2022
DOI: 10.21037/apm-22-525
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric palliative care through the eyes of healthcare professionals, parents and communities: a narrative review

Abstract: Background and Objective: Pediatric palliative care is a holistic approach that aims to enhance the quality of life of seriously ill children and their families. Despite the documented benefits, many barriers challenge early integration of such care. The lack of knowledge and negative attitudes and beliefs toward pediatric palliative care are often cited among these barriers. This narrative review aims to summarize the existing literature regarding knowledge, attitudes and beliefs toward pediatric palliative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
(126 reference statements)
0
11
0
1
Order By: Relevance
“…Os resultados destacam a importância de aumentar o conhecimento sobre o significado e o conteúdo do PPC entre os profissionais de saúde, a fim de manter a qualidade de vida de todas as crianças com condições limitantes ou com risco de vida ao longo de sua trajetória de doença. Saad et al (2022) As perspectivas dos profissionais de saúde foram mais exploradas em comparação com as amostras de pais e da comunidade. Os relatórios descrevem a confusão entre cuidados paliativos pediátricos e cuidados de fim de vida.…”
Section: Mcneilly Et Al (2022) Demonstram Modelos Reflexivos Frequent...unclassified
“…Os resultados destacam a importância de aumentar o conhecimento sobre o significado e o conteúdo do PPC entre os profissionais de saúde, a fim de manter a qualidade de vida de todas as crianças com condições limitantes ou com risco de vida ao longo de sua trajetória de doença. Saad et al (2022) As perspectivas dos profissionais de saúde foram mais exploradas em comparação com as amostras de pais e da comunidade. Os relatórios descrevem a confusão entre cuidados paliativos pediátricos e cuidados de fim de vida.…”
Section: Mcneilly Et Al (2022) Demonstram Modelos Reflexivos Frequent...unclassified
“…Similarly, wider community knowledge and understanding of paediatric palliative care was also often limited even when there was awareness or familiarity with the concept. However, and importantly Saad et al (9), found across multiple studies across professional, parent and community samples, when individuals are provided accurate information about paediatric palliative care, their attitudes towards it become more positive.…”
mentioning
confidence: 99%
“…Despite improvements to access and provision of paediatric palliative care services, particularly in higherincome countries, there are still significant barriers to access and integration globally (4-6). One significant barrier that remains, even when logistical, financial, and operational barriers are addressed is how palliative care is understood by health and social care professionals and families (7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond structural limitations like policy, resource and training, barriers to early integration of PPC to benefit from evidenced-proven outcomes persist, interestingly, within internal stakeholders. In this issue of the journal, Saad and colleagues reviewed extant literature to report cognitive and psychological factors that perpetuate this anomaly (3). Depending on whether the reader is already a convert, findings will uncover or deepen individual appreciation of entrenched ignorance and misconceptions among professionals, beneficiaries, and wider community.…”
mentioning
confidence: 99%